SLAVES OF CAPITAL: THE FUTURE OF WORKERS IN INDUSTRY 4.0 (CIPEEX, 2025)
The impact of industry 4.0 and technological innovation on the worker's reality is the object of this research. To this end, the research used qualitative-quantitative methodology with extensive bibliographical research. The problem to be addressed is how can industry 4.0 enslave workers? The relevance of the approach is justified, given that it seeks to assess the precariousness of work and also the loss of jobs due to technological innovation. The objective is to determine the impact of the 4.0 revolution on labor relations. Among the initial hypotheses are: one, evaluating how workers can adapt to innovation without losing their jobs. Another, how these innovations could lead to precarious work. The research results demonstrated that workers will be inserted into a regime of almost slavery when subjecting themselves to the needs imposed by industry 4.0. Finally, the study concluded that this new reality will limit workers' access to the world of work and will also require their extreme dedication to avoid losing their positions.
Keywords: Contemporary slavery; Industry 4.0; Technologic innovation; Precariousness